2016
DOI: 10.1177/2053168016683839
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a scale invariant relationship between the incumbency advantage and the nationalization of US House elections 1866–2014

Abstract: In a recent article, Jacobson examines the rise and fall of the incumbency advantage from 1952 to 2014. He shows that the incumbency advantage over this period rose as elections became more localized, and has fallen in recent decades as elections have become more nationalized. In this research note, we examine whether a similar relationship holds when we extend the time-series back to the end of the Civil War. Consistent with earlier work, we find that the scale of the incumbency advantage was much smaller in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Several recent studies, however, contend that the incumbency advantage is considerably smaller than it once was (Abramowitz and Webster 2016; Erikson 2016; Jacobson 2015; LeVeck and Nail 2016; Sievert and McKee 2019). Most notably, Jacobson (2015) illustrates that the electoral returns to incumbency have been in a steady decline since the 1980s.…”
Section: Incumbency Advantage In Congressmentioning
confidence: 94%
“…Several recent studies, however, contend that the incumbency advantage is considerably smaller than it once was (Abramowitz and Webster 2016; Erikson 2016; Jacobson 2015; LeVeck and Nail 2016; Sievert and McKee 2019). Most notably, Jacobson (2015) illustrates that the electoral returns to incumbency have been in a steady decline since the 1980s.…”
Section: Incumbency Advantage In Congressmentioning
confidence: 94%
“…voters are more likely to support incumbents over challengers (Jacobson and Jamie 2019;Snyder and Ansolabehere 2002). Importantly, however, scholars have recently found that the incumbency advantage has declined due, at least in part, to president-centered electoral nationalization (Carson, Sievert, and Williamson 2020;Jacobson 2015Jacobson , 2021LeVeck and Nail 2016). In short, the focus on national politics in many types of elections has "diminished…the opportunity for members to develop, through their own locally focused efforts, a personal relationship with constituents that can insulate them from national partisan forces, because deeper party divisions in the public have substantially reduced the number of voters susceptible to personal cross-party appeals" (Jacobson 2015, p. 869).…”
Section: Data and Measuresmentioning
confidence: 99%
“…Over the past several years, a series of studies has emerged documenting the growing correlation between presidential voting and voting for many different offices. Numerous studies, for example, have voting patterns in U.S. House elections are increasingly correlated with the presidential vote, and as a result, the value of incumbency has decreased over time (Carson, Sievert, and Williamson 2020;Jacobson 2015Jacobson , 2021LeVeck and Nail 2016). According to Jacobson's (2021) analysis, "the correlation between the district-level House and presidential vote…reached its highest point ever in 2020, an astonishing 0.987" (p. 13).…”
mentioning
confidence: 99%
“…House elections. 1 Scholars also agree that the average incumbency advantage has varied significantly over time (Gelman and King 1990;Carson, Sievert and Williamson 2019;LeVeck and Nail 2016). Since 1900, at least three different periods can be identified.…”
Section: Introductionmentioning
confidence: 98%
“…However, this type of analysis does not provide information about the phenomenon's temporal dynamics since a cross-sectional study offers solely a picture of a single point or period in time. Among those studies that have employed time-series analyses to investigate the causes of incumbency advantage (Ansolabehere and Snyder Jr 2002;Carson, Sievert and Williamson 2019;LeVeck and Nail 2016), none of them has estimated statistical models using incumbency advantage as the dependent variable.…”
Section: Introductionmentioning
confidence: 99%